Perfil epidemiológico e correlação entre comorbidades com o tempo de internação, desfecho e necessidade de ventilação invasiva em indivíduos com Covid-19 em um hospital de referência do estado do Pará, Brasil - DILLON, Alex de Oliveira (2023)
Objective: To trace an epidemiological profile and compare length of stay, outcome and need for invasive ventilation in patients with comorbidities and those without comorbidities in individuals hospitalized due to COVID19 in a referral hospital in the state of Pará, Brazil. Methods: This is a descriptive crosssectional study, conducted with the analysis of 67 medical records of individuals of both sexes. Data on sex, age group, comorbidities, length of hospital stay, outcome and use of invasive ventilation (IV) were collected, these data were stratified and correlated separately and with each other: presence or absence of comorbidity, outcome, length of stay x High blood pressure (HBP) x outcome, length of stay x Diabetes x outcome, VI x HBP and VI x Diabetes. The data obtained were analyzed using descriptive statistics using the Biostat 5.3 software. The study was approved by the Research Ethics Committee. Results: Sample revealed that half of the patients had comorbidities, and among all, 58% were discharged and 25% died. While those with comorbidities remained hospitalized longer and were the ones who died the most and required IV. Conclusion: It was possible to establish a correlation between chronically ill individuals and their outcomes. However, the correct filling of medical records is still precarious, with many unusable.